Preoperative prognostic nutritional index predicts short-term complications after radical resection of distal cholangiocarcinoma - He, Yulong; Liu, Haoran; Ma, Yuhu; Li, Jianlong; Zhang, Jinduo; Ren, Yanxian; Dong, Chunlu; Bai, Bing; Zhang, Yong; Lin, Yanyan; Yue, Ping; Meng, Wenbo (Frontiers in Surgery, 2023)
Background: The occurrence of postoperative complications of distal cholangiocarcinoma (dCCA) is an indicator of poor patient prognosis. This study aimed to determine the immune-nutritional indexes (INIs) that can predict short-term postoperative complications. Methods: A retrospective analysis of 148 patients with dCCA who were operated radical pancreaticoduodenectomy at the First Hospital of Lanzhou University from December 2015 to March 2022 was conducted to assess the predictive value of preoperative INIs and preoperative laboratory tests for short-term postoperative complications, and a decision tree model was developed using classification and regression tree (CART) analysis to identify subgroups at risk for overall complications. Results: In this study, 83 patients (56.08%) experienced overall complications. Clavien‒Dindo grade III-V complications occurred in 20 patients (13.51%), and 2 patients died. The areas under curves (AUCs) of the preoperative prognostic nutritional index (PNI), controlling nutritional status (CONUT) score, and neutrophil-to-lymphocyte ratio (NLR) were compared; the PNI provided the maximum discrimination for complications (AUC = 0.685, 95% CI = 0.600-0.770), with an optimal cutoff value of 46.9, and the PNI ≤ 46.9 group had higher incidences of overall complications (70.67% vs. 40.00%, P < 0.001) and infectious complications (28.77% vs. 13.33%, P = 0.035). Multivariate logistic regression analysis identified PNI (OR=0.87, 95% CI: 0.80-0.94) and total bilirubin (OR=1.01, 95% CI: 1.00-1.01) were independent risk factors for overall complications (P < 0.05). According to CART analysis, PNI was the most important parameter, followed by the total bilirubin (TBIL) level. Patients with a PNI lower than the critical value and TBIL higher than the critical value had the highest overall complication rate (90.24%); the risk prediction model had an AUC of 0.714 (95% CI, 0.640-0.789) and could be used to stratify the risk of overall complications and predict grade I-II complications (P<0.05). Conclusion: The preoperative PNI is a good predictor for short-term complications after the radical resection of dCCA. The decision tree model makes PNI and TBIL easier to use in clinical practice.